2019
DOI: 10.1103/physrevb.100.081101
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering from current-stabilized nonequilibrium phases in Ca2RuO4

Abstract: We used Raman light scattering to study the current-stabilized nonequilibrium semimetallic and metallic phases in Ca2RuO4. By determining the local temperature through careful analysis of the Stokes and anti-Stokes intensities, we find that Joule heating can be completely avoided by supplying sufficient cooling power in a helium-flow cryostat, and that the current induces the semimetallic state without inducing any significant heating. We further investigate the current-induced semimetallic state as a function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
(53 reference statements)
2
7
0
Order By: Relevance
“…S5). This voltage-current characteristics is consistent with the one observed in several previous experiments on Ca 2 RuO 4 under current flow [14,17,18,20,23,24]. With increasing current, the supplied electrical power increases (Fig.…”
Section: Current-driven Mitsupporting
confidence: 91%
See 2 more Smart Citations
“…S5). This voltage-current characteristics is consistent with the one observed in several previous experiments on Ca 2 RuO 4 under current flow [14,17,18,20,23,24]. With increasing current, the supplied electrical power increases (Fig.…”
Section: Current-driven Mitsupporting
confidence: 91%
“…3e. This indicates that the temperature sensors placed on the sample holder largely underestimate the actual temperature of Ca 2 RuO 4 which is heated up by the direct current, as also reported by a recent study by K. Fürsich et al [24]. This observation remarks the need for monitoring the local sample temperature as allowed by our imaging technique.…”
Section: Current-driven Mitsupporting
confidence: 77%
See 1 more Smart Citation
“…A prime example of this, is the family of ruthenates witch exhibits a rich and diverse phase diagram that includes Mott insulators 6,7 , unconventional superconductivity 8,9 , and magnetism 10,11 . The 4d electron Mott insulator Ca 2 RuO 4 6 (hereafter Ca214) has become the subject of intense research in recent years due to its intriguing electrical [12][13][14][15][16][17][18][19][20][21][22][23][24] and magnetic properties 25,26 . Specifically, at room temperature it undergoes a current-driven insulator to metal transition (IMT) which occurs at unusually low electric (E-)field or current density (J) thresholds (~40 V/cm or few A/cm 2 respectively) 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in a recent work, it was found that the IMT is always accompanied by a local temperature increase to the transition temperature 33 . Moreover, as a precursor to the metallic phase, a third and non-equilibrium (also called metastable) phase has been detected by X-ray and neutron diffraction experiments, and additionally with Raman spectroscopy [14][15][16] . This non-equilibrium phase seems to be induced by low current densities, but its role in the current-driven IMT remains elusive.…”
Section: Introductionmentioning
confidence: 99%